Alternatives to dental opioid prescribing after tooth extraction (ADOPT): protocol for a stepped wedge cluster randomized trial - Douglas R. Oyler; Philip M. Westgate; Sharon L. Walsh; Jennifer Dolly Prothro; Craig S. Miller; Monica F. Roberts; Patricia R. Freeman; Hannah K. Knudsen; Maggie Lang; Enif Dominguez-Fernandez; Marcia V. Rojas-Ramirez (BMC Oral Health, 2024)
Abstract Background Dentists and oral surgeons are leading prescribers of opioids to adolescents and young adults (AYA), who are at high risk for developing problematic opioid use after an initial exposure. Most opioids are prescribed after tooth extraction, but non-opioid analgesics provide similar analgesia and are recommended by multiple professional organizations. Methods This multi-site stepped wedge cluster-randomized trial will assess whether a multicomponent behavioral intervention can influence opioid prescribing behavior among dentists and oral surgeons compared to usual practice. Across up to 12 clinical practices (clusters), up to 33 dentists/oral surgeons (provider participants) who perform tooth extractions for individuals 12–25 years old will be enrolled. After enrollment, all provider participants will receive the intervention at a time based on the sequence to which their cluster is randomized. The intervention consists of prescriber education via academic detailing plus provision of standardized patient post-extraction instructions and blister packs of acetaminophen and ibuprofen. Provider participants will dispense the blister packs and distribute the patient instructions at their discretion to AYA undergoing tooth extraction, with or without additional analgesics. The primary outcome is a binary, patient-level indicator of electronic post-extraction opioid prescription. Data for the primary outcome will be collected from the provider participant’s electronic health records quarterly throughout the study. Provider participants will complete a survey before and approximately 3 months after transitioning into the intervention condition to assess implementation outcomes. AYA patients undergoing tooth extraction will be offered a survey to assess pain control and satisfaction with pain management in the week after their extraction. Primary analyses will use generalized estimating equations to compare the binary patient-level indicator of being prescribed a post-extraction opioid in the intervention condition compared to usual practice. Secondary analyses will assess provider participants’ perceptions of feasibility and appropriateness of the intervention, and patient-reported pain control and satisfaction with pain management. Analyses will adjust for patient-level factors (e.g., sex, number of teeth extracted, etc.). Discussion This real-world study will address an important need, providing information on the effectiveness of a multicomponent intervention at modifying dental prescribing behavior and reducing opioid prescriptions to AYA. ClinicalTrials.gov NCT06275191.